Performance budgeting and performance information in Poland and EU countries. Selected issues - Olejniczak, Jarosław (Budżet zadaniowy i informacja o wykonaniu zadań w Polsce i krajach UE. Wybrane zagadnienia, 2011)
In recent years most of the European countries have introduced different kinds of performance information and finally performance budgeting in order to support better public funds allocation. There is no single model of performance budgeting – it depends on each country’s approach to the use of performance information in the budgetary process. This article briefly reviews the European experience with performance budgeting and explores its application in Poland since 2006. It also presents the results of the OECD 2007/8 questionnaire on performance information for 25 EU members
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 44-55
Keywords: performance budgeting; state budget; government information policy